DRAMA LEARNING IN ELEMENTARY SCHOOL - Edi Sutarto; Emzir Emzir; Sabarti Akhadiah (Program Pascasarjana Universitas Negeri Jakarta, 2019)
This research aims to gain a deep understanding of drama learning in the 3 th grade of Athirah Islamic Elementary School 1 Makassar. To achieve the goal of the research, deeply investigation was done in the seven components of learning, namely the formulation of drama learning objectives, the selection of drama learning materials, the selection of drama learning methods, the selection of drama learning media, the role of learners in drama learning, the role of teacher in drama learning, and the drama evaluation system. This research is a qualitative ethnographic study, therefore, the data collection is done by observation, interviews, reviews of documentation, and reviews of records. The data analysis uses domain analysis, taxonomic analysis, componential analysis, and analysis of cultural themes. The results of the research show that drama learning in the 3 th grade of Athirah Islamic Elementary School 1 Makassar is being optimally by combining the systemic learning concept, the professional drama learning concept, and organizational culture concept which is one of the characteristics of Athirah Islamic Schools. Then these three aspects were merged into seven components of drama learning.